STUDY OF THE IMPACT OF ANESTHETIC INTERVENTION ON THE CONDITION OF NEWBORNS DELIVERED BY CESAREAN SECTION IN WOMEN WITH SEVERE MITRAL STENOSIS (Herald of the National Children's Medical Center, 2025)
The aim of this study was to comparatively assess the impact of different anesthetic techniques on the condition of newborns delivered by cesarean section from mothers with severe mitral stenosis. A total of 38 neonatal case histories were analyzed and divided into two groups based on the anesthesia method used: general multicomponent anesthesia (GMA) with mechanical ventilation and combined anesthesia (CA) based on epidural blockade with reduced concentrations of local anesthetics. It was found that CA has a less pronounced stress and depressive effect on the functional state of newborns, improving Apgar scores, NACS, stress index, and oxygen saturation, while also contributing to more effective endocrine adaptation. The results obtained support the recommendation of CA as the preferred method of anesthesia for parturients with severe mitral stenosis.
Keywords: newborns; cesarean section; mitral stenosis; anesthesia; epidural block; cortisol; adaptation